Macrolide Resistance in Streptococcus pneumoniae - Schroeder, Max R.; Stephens, David S. (Frontiers in Cellular and Infection Microbiology, 2016)
Streptococcus pneumoniae is a common commensal and an opportunistic pathogen. Suspected pneumococcal upper respiratory infections and pneumonia are often treated with macrolide antibiotics. Macrolides are bacteriostatic antibiotics and inhibit protein synthesis by binding to the 50S ribosomal subunit. The widespread use of macrolides is associated with increased macrolide resistance in S. pneumoniae, and the treatment of pneumococcal infections with macrolides may be associated with clinical failures. In S. pneumoniae, macrolide resistance is due to ribosomal dimehtylation by an enzyme encoded by erm(B), efflux by a two-component efflux pump encoded by mef(E)/mel and, less commonly, mutations of the ribosomal target site of macrolides. A wide array of genetic elements have emerged that facilitate macrolide resistance in S. pneumoniae; for example erm(B) is found on Tn917, while the mef(E)/mel operon is carried on the 5.4- or 5.5-kb Mega element. The macrolide resistance determinants, erm(B) and mef(E)/mel, are also found on large composite Tn916-like elements most notably Tn6002, Tn2009, and Tn2010. Introductions of 7-valent and 13-valent pneumococcal conjugate vaccines (PCV-7 and PCV-13) have decreased the incidence of macrolide-resistant invasive pneumococcal disease, but serotype replacement and emergence of macrolide resistance remain an important concern.